Psychometric Validity of the Indonesian People Democratic Attitude Scale - Wahyu Syahputra; Devie Yundianto; Bay Dhowi; Nurlia Dian Paramita (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2023)
the Indonesian People Democratic Attitude Scale was designed to measure democratic attitudes with a sample of Indonesian society. It has six dimmension: democratic culture, democratic rights and equality, duties and responsibilities, democratic participation, global citizenship, and citizenship values. The present study investigate to construct validity of the scale scores. The sample in this study consisted of 737 participants from various elements of society throughout Indonesia, with an age range of 17 – 80 years (mean age = 38.60; SD = 10.37). The sample consisted of 536 males and 204 females. Factor Analysis found that this scale is psychometrically sound and this scale can positively contribute to various elements of Indonesian society to know about a person's democratic attitude